Rice lipid transfer protein, OsLTPL23, controls seed germination by regulating starch-sugar conversion and ABA homeostasis - Li, Quanlin; Zhai, Wenxue; Wei, Jiaping; Jia, Yanfeng (Frontiers in Genetics, 2023)
Seed germination is vital for ensuring the continuity of life in spermatophyte. High-quality seed germination is a prerequisite event for seedling establishment and crop yield. Here, we identified OsLTPL23, a putative non-specific lipid transport protein, as an important regulator responsible for seed germination. Subcellular localization analysis revealed that OsLTPL23 is localized in the plasma membrane and nucleus. The knockout mutants of OsLTPL23 were generated by CRISPR/Cas9-mediated genome editing, and osltpl23 lines significantly germinated slower and lower than the Nipponbare (NIP). Starch and soluble sugar contents measurement showed that OsLTPL23 may have alpha-amylase inhibitor activity, and soluble sugar is a causal agent for the delayed seed germination of osltpl23 mutants. Transcript profiles in the germinating seeds exhibited that the ABA-responsive genes, OsABI3 and OsABI5, and biosynthesis genes, OsNCED1, OsNCED2, OsNCED3 and OsNCED4, are obviously up-regulated in the osltpl23 mutants compared to NIP plants, conversely, ABA metabolism genes OsABA8ox1, OsABA8ox2 and OsABA8ox3 were stepwise decreased. Further investigations found that osltpl23 mutants displays weakened early seedling growth, with elevated gene expresssion of ABA catabolism genes and repressive transcription response of defence-related genes OsWRKY45, OsEiN3, OsPR1a, OsPR1b and OsNPR1. Integrated analysis indicated that OsLTPL23 may exert an favorable effect on rice seed germination and early seedling growth via modulating endogenous ABA homeostasis. Collectively, our study provides important insights into the roles of OsLTPL23-mediated carbohydrate conversion and endogenous ABA pathway on seed germination and early seedling growth, which contributes to high-vigor seed production in rice breeding.